Mitigation and risk management of climate change in crop cultivation through the adoption of Agromet Advisory Bulletin (AAB) in NICRA adopted villages in Punjab (MAUSAM, 2024)
Crop production is a direct output of manageable (agronomic) and unmanageable (weather) inputs. A farmer can cut down losses in crop production due to aberrant weather conditions by following weather forecast. India Meteorological Department is providing weather forecast on eight weather parameters at district and block level. Under All India Coordinated Research Project on Agrometeorology-National Innovations in Climate Resilient Agriculture, an Agromet Advisory Bulletin (AAB) is prepared by using this forecast for coming five days and disseminated to farmers. To evaluate the impact of AAB in three selected villages Badoshe Kalan and Bauranga Zer (district Fatehgarh Sahib) and Rampur Fasse (district Rupnagar) a survey from 110 farmers was conducted. Amongst the 110 farmer, 70 were marginal/small farmers (landholding